ANALISIS DENSITAS KELURUSAN DAN HUBUNGANNYA DENGAN DISCHARGE AREA DI DAERAH GUNUNG TAMPUSU DAN SEKITARNYA - Mersel Sumigar; Alfrits Komansilan; Marianus (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Mount Tampusu, Minahasa Regency, North Sulawesi has geological conditions that are influenced by the geothermal system. Where the geothermal system has plate movement that affects it, one of which is the convergent plate movement, where two plates collide with each other, resulting in the potential for surface manifestation. This study aims to analyze the surface structure and discharge area or commonly referred to as geothermal manifestations based on the density of straightness and surface manifestations. The structure on the surface was analyzed by lineament density using the FFD method. It is assumed that the fracture or fault is associated with geothermal areas which are mostly difficult to identify because they are covered by surface manifestations. Faults and fractures are the pathways for the movement of hot fluids because they are assumed to be weak fields so that they can be clues to the location of the discharge area or manifestation. Based on the FFD and Remote Sensing Methods collaborated with satellite image data, the surface density and its relationship with the discharge area in the study area were known. Where there are 64.45 straight ridges and valleys in the area with density values ​​ranging from 1.6 to 4.6.